Communication and Information Sharing in Teams - Rothenberg, Naomi R. (The Accounting Review, 2015)
ABSTRACT This paper studies whether dissemination of private, pre-decision signals about productivity is valuable to the principal when agents work sequentially and observe each other's effort. The benefit of dissemination is that when productivity states are correlated, each agent's signal is useful as a performance measure for the other agent and for making efficient production choices. The more informative the signal is about agents' efforts, the greater the benefit of the additional performance measure, but there is a cost due to higher information rents. With no dissemination, the downstream agent learns about the upstream agent's productivity state by observing that agent's effort. The upstream agent's rents are lower because he has no incentive to free-ride on the downstream agent, who follows his effort, but there is less information on which to base the payments. The choice between dissemination and no dissemination depends on the informativeness of the signal about agents' efforts. JEL Classifications: D82; D83; J41; M41.